Про стан та перспективи розвитку фізики фероїків в Україні (за матеріалами наукової доповіді на засіданні Президії НАН України 13 грудня 2017 року) - Морозовська, Г.М. (Вісник НАН України, 2018)
Доповідь охоплює широке коло питань, що мають важливе значення для вирішення актуальних проблем розвитку фізики фероїків в Україні. Зазначено, що фероїки є унікальними об’єктами для фундаментальних фізичних досліджень складних нелінійних процесів і явищ, які відбуваються в цих речовинах у мікро- і наномасштабі. Завдяки можливості керування фізичними властивостями фероїків за допомогою розмірних ефектів наноструктури на їх основі є одними з найперспективніших для застосувань у наноелектроніці, наноелектромеханіці, оптоелектроніці, нелінійній оптиці та інформаційних технологіях. У НАН України сформувалася наукова школа з фізики фероїків, характерною ознакою якої є глибока інтегрованість у міжнародну наукову спільноту. Українські вчені отримали ряд пріоритетних результатів, які мають фундаментальне значення для розуміння нелінійних фізичних процесів у нанофероїках, а також є важливими для їх новітніх застосувань у наноелектроніці. The report covers a wide range of important issues concerning the state-of-art of ferroics physics in Ukraine. It is noted that ferroics are substances with a long-range order parameter - spontaneous magnetization (ferromagnetics), polarization (ferroelectrics) or strain (ferroelastics), which arise as a consequence of phase transition taking place with the temperature decrease. Substances having more than one of the interacting long-range orders are called multiferroics. Ferroics and multiferroics are unique objects for fundamental physical research of complex nonlinear processes and phenomena, which occur in them on the micro and nano-scale. Due to the possibility of controlling the physical properties of ferroics with the help of size effects, nanostructures on their basis are among the most promising for applications in nanoelectronics, nanoelectromechanics, optoelectronics, nonlinear optics and information technologies. The National Academy of Sciences of Ukraine has formed the world-recognized school of ferroics, and its characteristic features are deep integration into the international scientific community and effective collaboration between the scientific groups of the National Academy of Sciences of Ukraine. Ukrainian scholars received a number of priority results that brought the Ukrainian school of ferroics to the forefront of the world. Over the past 10 years, it has been found that the thickness of the strained films, the size and shape of the ferroic and multiferroic nanoparticles are unique tools for controlling their phase diagrams, long-range order parameters, magnitude of susceptibility, magnetoelectric coupling and domain structure characteristics at fixed temperature. Significant influence of the flexo-chemical effect on the phase transition temperature, polar and dielectric properties of nanoparticles is revealed. It is established that the flexocoupling can induce a soft acoustic mode and incommensurate spatially-modulated phases in ferroelectrics. Obtained results are important for understanding of the nonlinear physical processes in nanoferroics, for the interpretation of the scanning probe and tunneling electron microscopy results, as well as for the advanced applications in nanoelectronics.